Integrated PWM solar charge controller and DCDC converter using fixed-frequency current control mode for reducing selfpower consumption of off-grid solar home system / Mohammad Shariful Islam - Islam, Mohammad Shariful (2024)
The Solar Home System (SHS) stands as a dependable and sustainable solution for powering remote areas without grid access. However, the development of SHS packages faces technical hurdles encompassing self-power consumption, advancements in PWM solar charge controllers, DC-DC converters, and integrating solar charging with voltage conversion in off-grid setups. Despite the efficiency of solar charge controllers, their affordability for smaller systems remains a concern. In addressing these challenges, this study introduces a comprehensive integration method. This method combines a single-stage boost DC-DC converter with an analog PWM solar charge controller using a fixed frequency current control mode algorithm. Through simulation studies, this approach showcases practicality and cost-effectiveness, significantly reducing the number of devices required for off-grid SHS while preserving functionalities similar to AC power systems. Key findings highlight enhanced controller features with essential safety measures, the development of an integrated controller, and a notable decrease in self-power consumption through innovative push-button switch mechanisms. The study systematically resolves technical design challenges, offering a holistic solution that enhances efficiency and cost-effectiveness in off-grid SHS. The resulting integrated system, operating in a fixed frequency current control mode, undergoes rigorous testing. It demonstrates remarkable performance with a maximum load capacity of 350 watts and exceptionally low self-power consumption of 16.89 mW. Furthermore, this integration minimizes required solar panel size without compromising essential system features, attributed to the notable decrease in self-power consumption achieved by the combined device. These achievements affirm the viability, effectiveness, and affordability of the developed controller, presenting a promising path to encourage sustainable energy consumption in underserved communities and drive progress towards a greener future.